Polysaccharides of Dendrobium officinale Kimura & Migo Leaves Protect Against Ethanol-Induced Gastric Mucosal Injury via the AMPK/mTOR Signaling Pathway in Vitro and vivo - Ke, Yang; Zhan, Lianghui; Lu, Tingting; Zhou, Cong; Chen, Xue; Dong, Yingjie; Lv, Guiyuan; Chen, Suhong (Frontiers in Pharmacology, 2020)
Ethanol-induced gastric mucosal injury is a common gastrointestinal disorder. Polysaccharides separated from herbs has been shown effective of ethanol-induced gastric mucosal injury, but it was not clarified whether the polysaccharides came from Dendrobium officinale leaves (LDOP) protected mucosa from ethanol-induced injury. Thus, the present study was carried out gastric mucosal protection and the mechanism of LDOP in vivo and vitro. The results showed that LDOP significantly reduced gastric mucosal injury score and pathological injury, improved antioxidant capacity, reduced the level of ROS and reversed the apoptosis of GES-1 cells in vivo and vitro. Mechanism research showed that LDOP pretreatment upregulated the expression of p-AMPK, LC3β, HO-1, Beclin-1, downregulated the p-mTOR and p62, reversed the expression of Caspase3, Bax and Bcl-2. In one word, the study was the first one to demonstrate that LDOP could protect ethanol-induced gastric mucosal injury via AMPK/mTOR signaling pathway in vitro and vivo.